2009
DOI: 10.1007/978-1-60761-369-5_4
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Neural Differentiation of Human Embryonic Stem Cells Using a Low-Density Mouse Embryonic Fibroblast Feeder Protocol

Abstract: Human embryonic stem cells (hESCs) have the capacity to self-renew and to differentiate into all components of the embryonic germ layers (ectoderm, mesoderm, endoderm) and subsequently all cell types that comprise human tissues. HESCs can potentially provide an extraordinary source of cells for tissue engineering and great insight into early embryonic development. Much attention has been given to the possibility that hESCs and their derivatives may someday play major roles in the study of the development, dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Standard pluripotent hESCs are maintained by growing them on mouse embryonic fibroblasts (MEF) and routinely passaging them to prevent unwanted spontaneous differentiation. A reduction in MEF-secreted pluripotency factors by hESC culture on low-density MEFs encourages spontaneous neurectoderm differentiation [19][20][21][22], whereas bone morphogenic protein 4 (BMP4) supplementation to MEFs at low density [23,24] produces TE from pluripotent hESCs. However, the factors responsible for initiating human TE differentiation from pluripotent hESCs, that is TE induction, are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Standard pluripotent hESCs are maintained by growing them on mouse embryonic fibroblasts (MEF) and routinely passaging them to prevent unwanted spontaneous differentiation. A reduction in MEF-secreted pluripotency factors by hESC culture on low-density MEFs encourages spontaneous neurectoderm differentiation [19][20][21][22], whereas bone morphogenic protein 4 (BMP4) supplementation to MEFs at low density [23,24] produces TE from pluripotent hESCs. However, the factors responsible for initiating human TE differentiation from pluripotent hESCs, that is TE induction, are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the number of adherent cells was significantly reduced when compared with the other groups when the same number of cells were seeded. Taking into account that the density of the feeder cells may influence the maintenance of hESCs (6,2628), cell numbers were increased in the −70°C 60 day group in order to provide a number of adherent cells that was consistent with those in the other groups. Even though the cell number was supplemented, it was observed that the proliferation rate of the hESCs was slower in the −70°C 60 day group than that of the other groups from the beginning of the third generation; hESC colonies on the feeder were evidently differentiated (loosely arranged with no clear boundary, thin clumps and morphological heterogeneity).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several diverse cell types have been derived from hESCs, including cardiomyocytes [66,67], endothelial cells [68][69][70], chondrocytes [71][72][73][74][75], osteoblasts [76][77][78], neurons [79][80][81], keratinocytes [82,83], and hepatocytes [84].…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%